The Welfare State, Globalization, and International Law
XXII, 448 p.
Keywords: Globalization imposes pressures on the traditional welfare state. This book examines these pressures, and responses to them, from the less familiar perspective of international law. The book deals with the role of the international level in securing or supplementing national welfare functions. Thus, the authors evaluate the role of international labour law, social rights as human rights, the World Trade Organisation, non-governmental organisations and international taxation law, in the effort to maintain and promote welfare rights and the welfare state. In addition, the functions of national migration law and of social security law are analysed in case studies.